2007
DOI: 10.1074/mcp.m600431-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Membrane Protein Overexpression in Escherichia coli

Abstract: Overexpression of membrane proteins is often essential for structural and functional studies, but yields are frequently too low. An understanding of the physiological response to overexpression is needed to improve such yields. Therefore, we analyzed the consequences of overexpression of three different membrane proteins (YidC, YedZ, and LepI) fused to green fluorescent protein (GFP) in the bacterium Escherichia coli and compared this with overexpression of a soluble protein, GST-GFP. Proteomes of total lysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
217
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(239 citation statements)
references
References 74 publications
(44 reference statements)
7
217
1
5
Order By: Relevance
“…We found that in E. coli this gene presents an iTSS (TSS_873, locus b0733) for a putative intraRNA that, if translated using the first available ATG start codon 29 nt downstream, would produce a 43.9 kDa isoform of the 58.2 kDa CydA cognate protein. Mass spectrometry identification of spots in 2D gels of cytoplasmic membranes performed ten years ago [70] showed CydA (among others) spots with observed MW incompatible with full-length protein but consistent with isoform. Contrary to previous examples, this protein is not highly acidic and do not meet the criteria for MW correction.…”
Section: Resultsmentioning
confidence: 99%
“…We found that in E. coli this gene presents an iTSS (TSS_873, locus b0733) for a putative intraRNA that, if translated using the first available ATG start codon 29 nt downstream, would produce a 43.9 kDa isoform of the 58.2 kDa CydA cognate protein. Mass spectrometry identification of spots in 2D gels of cytoplasmic membranes performed ten years ago [70] showed CydA (among others) spots with observed MW incompatible with full-length protein but consistent with isoform. Contrary to previous examples, this protein is not highly acidic and do not meet the criteria for MW correction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the concentrations of E,Z-PAOx and PAN in the culture broths of the ATCC 31882 transformants were far lower than those of the C41(DE3) transformants, probably due to the lower biomass concentrations of the ATCC 31882 transformants than the C41 transformants. These negative results for the ATCC 31882 transformants can be explained by its lower tolerance of heterologous expression of the membrane proteins than the C41 strain (42). Thus, it was suggested that in addition to the ability to biosynthesize L-Phe, the tolerance of a host cell for heterologous expression of membrane protein has to be improved to increase the concentrations of E,Z-PAOx and PAN.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Both the forward and side scatters of ghosts and control cells were monitored, which allowed comparing their size and internal complexity, respectively (32)(33)(34). The size (forward scatter) of a large fraction of the ghosts resembled the size of the control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EC452 was cultured as described above; IPTG was added to the culture at an OD 600 of 0.25 for induction of gfp expression (see "Strains, plasmids, and culture conditions" above) and E gene expression was subsequently induced at an OD 600 of 0.5 by the addition of 6 mM L-rhamnose. EC452 cells/BGs were harvested immediately before lysis induction and 120 min after induction, treated as described above, and stained with the membrane dye FM4-64 as described before (32). Prior to imaging, cells were placed on a microscope glass slide coated with a premade agarose pad (1% [wt/vol] agarose) and were left to immobilize for ϳ5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation